LES INITIATIVES DE REFORME DU SECTEUR DE LA SECURITE DE L’AMISOM : QUEL IMPACT SUR LA SECURITE DE LA SOMALIE ? - NZE BEKALE, Ladislas (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
AMISOM Security Sector Reform Initiatives: What Impact on the Security of Somalia? In the context of the post conflict reconstruction of the State in Somalia the AMISOM has undertaken the reform of the security sector. The African Union mission activities are mainly focused on the strengthening of the capacity of the national security and defense forces to enable these actors to take over the entire security of the country as soon as possible. Despite the engagement of the AMISOM forces terrorist groups are still very active, maintaining the country in a certain insecurity and uncertainty.